LENGTH DISTRIBUTION AND SEX RATIO TO INVESTIGATE SPAWN ELIGIBILITY OF BIGEYE TUNA(THUNNUS OBESUS LOWE, 1839) IN THE INDIAN OCEAN - Arief Wujdi; Fathur Rochman; Irwan Jatmiko (Widyariset, 2016)
Bigeye tuna (Thunnus obesus Lowe, 1839) is the important commodity for the fishing industry in Indonesia. Increased exploitation is threatening their population, so that is necessary to monitor the size composition that meets the eligibility to be captured, as well as the sex ratio as a management measure. Data was collected by scientific observers program which was following commercial tuna longline operation mainly based in Benoa, Palabuhanratu and Bungus Fishing Port from August 2005 to December 2014. Chi-Square analysis with 95% of confidence level also implemented to determine the sex ratio of female and male. The result showed that BET caught ranged from 30 to 192 cm, mode size ranged from 121 to 125 cm and mean 111,76 cm. As much as 69,5% of them was greater than a length at first maturity (Lm) and that means have been worthy to be captured. The sex ratio of (F:M) 1:1,32 was observed which indicates male was  dominant  than  female.  Correlation  between  sex  ratio  and  length proved to be significant where the female was increasing in size between 95-145 cm, as described a regression equation. However, an equal sex ratio occurred during December to January and also from April to June along the southern part of Java and East Nusa Tenggara and western part of Australia waters.